PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME PADA MATERI KELIPATAN DAN FAKTOR BILANGAN DI KELAS IV SDN 26 GASAN KECIL KABUPATEN AGAM - Saswita, Rika; Harisman, Yulyanti; Melisa, Melisa (Pendidikan Matematika, 2014)
ABSTRACTÂ The 4th grade Students on SDN 26 Gasan Kecil has used rely on one book for mathematical learning process. Therefore most difficult for them to understanding especially for the Multiple Numbers and Factors of Numbers. They have not been able to knowleage constructs. This research is for create a constructivisme valied module. The metode of this study are Research and Development with using of 4-D models in consists of 4 phases: definition or requirements analysis, design, development and the disseminate. However, the stages through which this research is only up to the third stages development the are validity, efektivity and practicability. However from these 3rd phak used for validity only. The conclusion of the Module validation are Very Valid in Terms of Content and Constructs. At this s;tage of the obtained results module validity can be used for learning process for 4th Grades of SDN 26 Gasan Kecil.